Pengembangan Multimedia Interaktif Berbasis Problem Solving Pada Siswa Kelas Xi Sma N 1 Suruh Kab. Semarang - Kristiyono, Agus; , Prof. Dr. Budi Murtiyasa, M.Kom; , Idris Harta, M.A.Ph.D (2016)
This research is aimed to know the media learning currently used in SMA N 1 Suruh and to develop interactive multimedia based on problem solving. The final results of the study tested the effectiveness using interactive multimedia based on problem solving.The research method used is a Research and Development which covers introduction, field study, draft model of interactive multimedia, limited testing,wider testing, and implementation of learning using interactive multimedia based on problem solving. The subject of research is all students of class XI in SMA N 1 Suruh. Data collection techniques used are documentation, observation, interview, assessment and test. Data analysis used is qualitative and quantitative techniques. The research found that the learning of mathematics in SMA N 1 Suruh still conventional and learning using information technology is still rarely applied. The development of interactive multimedia based on problem solving as a medium of learning is very eligible used by the validator with an average percentage of 87,35%. The results of student learning on a limited testing is 32.61% where as in the wider testing is 40.00%. Interactive multimedia basedon problem solving applied to all students of Class XI SMA N 1 Suruh is effective. The response of the students to the use of interactive multimedia based on problem solving in learning mathematics is very eligible with a percentage of 89,00%. The use of interactive multimedia based on problem solving to all students of class XI SMA N 1 Suruh can encourage students to learn independently as well as with the guidance of teachers, easy to understand the concept of material in achieving learning objectives, and motivate students.